Ir(III)-catalyzed synthesis of isoquinoline N-oxides from aryloxime and alpha-diazocarbonyl compounds - Phatake, Ravindra S.; Patel, Pitambar; Ramana, Chepuri V. (Organic Letters, 2016)
An efficient Ir(III)-catalyzed C-H activation and annulations of aryloxime with a-diazocarbonyl compounds has been developed for the synthesis of substituted isoquinoline N-oxides. The reaction proceeds under mild atmospheric conditions, without any external oxidants and releases N-2 and H2O as the byproducts. In addition, synthetic applications of the N-oxide products have been established by performing further functionalization. An interesting dimeric iridacyclic complex allied through a bis-silver carboxylate bridge has been isolated that efficiently catalyzed the reaction.